MATURATION AND OVULATION INDUCTION IN COMET FISH Carassius auratus auratus OUTSIDE THE SPAWNING SEASON - Dhewantara, Yudha Lestira; Nainggolan, Armen; Yarto; Epram (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2025)
The aim of this study was to evaluate the administration of Oodev® hormone and turmeric powder (Curcuma longa) on gonadal maturation and to assess the effectiveness of Spawnprim hormone for ovulation and spawning to support the production of comet fish (Carassius auratus auratus), particularly outside the spawning season. The maturation doses of the test substances mixed into the feed were as follows: Treatment 1: Commercial feed (without test substance); Treatment 2: Oodev 0.25 mL kg⁻¹ fish; Treatment 3: Oodev 0.5 mL kg⁻¹ fish; Treatment 4: Turmeric powder 250 mg 100 g⁻¹ feed + Oodev 0.5 mL kg⁻¹ fish; Treatment 5: Turmeric powder 250 mg 100 g⁻¹ feed. Meanwhile, for ovulation induction, the injections were administered as follows: Treatment 1: Spawnprime 0.5 mL kg⁻¹ broodstock; Treatment 2: Spawnprime 1 mL kg⁻¹ broodstock; Treatment 3: Ovaprim 0.5 mL kg⁻¹ broodstock; Treatment 4: 0.9% NaCl solution 0.5 mL kg⁻¹ broodstock. The optimal dose for stimulating gonadal maturation until the broodstock was ready to spawn reached 30% of the population within 40 days outside the spawning season. Spawnprime can serve as a substitute for Ovaprim, as it demonstrated a 100% ovulation success rate and spawning outcomes comparable to those of Ovaprim.